1993
DOI: 10.1177/095148489300600204
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Surgical Efficiency in Independent Practice Association HMOS and Traditional Insurance Programs

Abstract: This study examines the effect of Independent Practice Association (IPA) HMO membership on hospital total charges, ancillary charges and length of stay (LOS) for surgical patients. Intrahospital comparisons of IPA and traditional insurance patients are made after adjusting for surgical procedure, admission severity of illness, age, sex and year of admission. Our multiple regression model indicates that IPA patients undergoing 12 frequently occurring surgical procedures have lower resource use. Eight (80%) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…Patients treated under health maintenance organizations have significantly shorter times in the hospital than those treated under fee-for-service plans [53, 54]. It would be useful to study the impact of implementing different payment systems on LOS simultaneously with various factors affecting LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated under health maintenance organizations have significantly shorter times in the hospital than those treated under fee-for-service plans [53, 54]. It would be useful to study the impact of implementing different payment systems on LOS simultaneously with various factors affecting LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Bradbury et al [18] compared a specific type of HMO with traditional insurance programs by hospital, thus keeping hospital characteristics constant. Due to the fact that there had to be enough admissions of both types of insurance to a hospital for ordinary regression analysis to be possible, only ten (of the initial 78) hospitals were included in the analyses, a problem that could have been overcome with multi-level analysis.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Using ordinary regression analysis, it was found that the way patients are insured [17,18] and physicians are paid [19] significantly influences length of stay. A review carried out by Miller and Luft [20] reported that length of stay was shorter for patients in Health Maintenance Organizations (HMOs; a managed care organization), in fifteen out of sixteen observations from thirteen studies using data from 1980 onwards.…”
Section: Introductionmentioning
confidence: 99%
“…In amerikanischen Managed-Care-Modellen konnten eine bis zu 40% geringere Rate an Krankenhauseinweisungen und eine bis zu 35% verkürzte Verweildauer der Patienten im Krankenhaus erreicht werden [6,[9][10][11][12]. Die Anzahl der Krankenhaustage pro 1000 Versicherte und Jahr lag in Managed-Care-Modellen bis zu 33% niedriger als in konventionellen Versorgungssystemen [13,14].…”
Section: Chancen Von Managed Careunclassified